Sedimentary environment analysis of the Asmari Formation (Upper Rupelian) based on microfossils in Bandar Abbas Hinterland, south Iran - Jahanbakhsh Daneshian; Mahboobeh Sadat Tabatabaei; Alireza Tahmasbi (Journal of Stratigraphy and Sedimentology Researches)
AbstractIn this research, facies distribution and sedimentary environment of the Asmari Formation have been studied in Bandar Abbas Hinterland, located in southern Iran. For this purpose, two outcrop sections including Khamir and Gachestan have been selected in this area. The study of thin sections of Khamir (160 m-thick) and Gachestan sections (220 m-thick) and their components led us to identify nine microfacies. In this research, the role of microfossils, especially foraminifera is investigated in the detection of microfacies and sedimentary environment. Based on the sedimentary texture and the type of fossils, the depositional environments were identified. The components are mostly larger benthic foraminifera and red algae, which indicate the middle ramp, and also the accumulation of imperforate foraminifera, which indicates the inner ramp. Based on this, the sedimentary model for the Asmari Formation in the study area was attributed to a carbonate ramp, which can be divided into three sub-environments: inner, middle and outer ramp.Keywords: Asmari Formation, Rupelian, depositional environments, Bandar Abbas Hinterland  IntroductionThe carbonates of the Asmari Formation are the main petroleum reservoir rock in the Zagros Basin. Primary works concerning the Asmari Formation are attributed to Busk and Mayo (1918), Richardson (1924 and Thomas (1948). The age of this rock unit is Oligocene to Early Miocene (Burdigalian). In Fars province, this formation belongs to the Oligocene, while in Khuzestan, the age is Oligocene to Early Miocene and towards the basin center, this rock unit belongs to Early Miocene (Aquitanian–Burdigalian). Considering the importance of the Asmari Formation in the Zagros Basin and the fact that studies conducted on this formation have been mostly in the Fars and Izeh zones, this study focuses on depositional environment reconstruction of the Asmari Formation in Bandar Abbas hinterland in southern Iran. Materials & MethodsThe study is based on two outcrops in Bandar Abbas hinterland in southern Iran. Kuh-e Khamir section with coordinates of 27°, 00ʹ, 35ʹʹ N and 55°, 35ʹ, 13ʹʹ E, and Gachestan section with coordinates of 26°, 54ʹ, 04ʹʹ N and 54°, 05ʹ, 22ʹʹ E. The microfacies studies are based on 250 thin sections of the examined sections. All thin sections were analyzed under the microscope for biostratigraphy and facies. The classification of carbonate rocks followed the nomenclature of Dunham (1962) as well as the modified scheme of Embry and Klovan (1971). In addition, microfacies were determined based on Flügel (2020).   Discussion of Results & ConclusionsFacies analysis of the Asmari Formation in study outcrops including Khamir (160 m-thick) and Gachestan (220 m-thick) sections resulted in the definition of nine microfacies types as follows:Bioclastic planktonic foraminifera wackestone/packstone (MF1): The presence of planktonic foraminifera, muddy matrix and lack of sedimentary structures suggest that this facies were deposited in calm and deep, normal-salinity seawater below the storm wave base.Bioclastic Nummulitid packstone/grainstone (MF2): Abundance of larger and flat nummulitids with some planktonic foraminifera suggest low-medium energy, open-marine environment, and between the storm and fair-weather wave base.Bioclastic nummulitid red algae floatstone/packstone (MF3): The presence of corallinacean algae and larger benthic foraminifera suggest a distal part of inner to mid-ramp sub-environments and indicate an oligophotic zone.Bioclastic coral- red algae floatstone/rudstone (MF4): This facies is interpreted to have been deposited under shallow water with moderate energy below the fair-weather wave base in the middle ramp sub-environment.Bioclastic imperforate foraminifera nummulitid packstone (MF5): The faunal composition indicates that sedimentation took place in the lagoon with normal circulation and well-oxygenated waters. The presence of large porcelaneous foraminifers associated with Nummulitid suggests deposition in the euphotic zone in an open-lagoonal environment.Bioclastic imperforate foraminifera packstone (MF6): This facies represents a high-energy, shallow-water setting influenced by wave and tide processes. In addition, the presence of Peneroplis and Archaias in this facies indicates a sea grass-dominated environment.Bioclastic small benthic foraminifera echinoid wackestone/packstone (MF7): The low diversity of fauna (small rotaliids and echinoid debris) suggests a low-energy environment in the shallow water of the inner ramp sub-environment.Bioclastic miliolids wackestone/packstone (MF8): This microfacies is interpreted as the restricted shallow inner ramp sub-environment. Low diversity and abundance of imperforate foraminifera and mud-rich facies indicate deposition in a low-energy, restricted shallow lagoon.Mudstone (MF9): Accumulation of carbonate mud suggests the low energy conditions in the lagoonal-peritidal and proximal inner ramp sub-environment.A detail study of the Asmari Formation in two outcrop sections represents the development of a carbonate ramp as a sedimentary model during the Rupelian. The Carbonate ramp can be divided into three inner, middle and outer ramp sub-environments their boundary can be distinct based on the water depth of fair-weather wave and storm wave base. In this study outer ramp represents with microfacies MF1 and the dominant fauna is planktonic foraminifera. The middle ramp is shown with the presence of microfacies 2–4 (MF2–4). This environment is dominant in large benthic foraminifera, red algae and coral. The inner ramp setting is represented by an abundance of imperforate foraminifera, so microfacies 5 to 9 (MF5–9) are deposited in this sub-environment.